Eksplorasi Karakteristik Mahasiswa Ekstrovert dalam Proses Interaksi Sosial di Kelas - Ramadhani, Rara Putri; Sri Nurhayati Selian (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2026)
This study was conducted to understand how extroverted student characteristics emerge in social interactions in the classroom. The background of the study indicates that social interaction is a crucial component of the learning process in higher education, and extroverted personality plays a significant role in enhancing active participation, interpersonal engagement, and social dynamics in students. This study used a descriptive qualitative approach. The subjects consisted of three students with extroverted personality tendencies selected through purposive sampling to ensure relevant information. Data were collected through observation, semi-structured interviews, and documentation, then systematically analyzed. The results showed that extroverted students actively participated in class discussions, expressed opinions, and engaged cognitively, emotionally, and socially. This improved communication skills, self-confidence, and optimal understanding of the material, contributing to a comprehensive and effective classroom learning process for all students in various learning situations.